Encapsulation of Ammoides pusila Essential Oil into Mesoporous Silica Particles for the Enhancement of Their Activity against Fusarium avenaceum and Its Enniatins Production - Yasmine Chakroun; Youssef Snoussi; Mohamed M. Chehimi; Manef Abderrabba; Jean-Michel Savoie; Souheib Oueslati (Molecules, 2023)
Essential oils (EOs) that have antifungal activity and mycotoxin reduction ability are candidates to develop bioactive alternatives and environmentally friendly treatment against Fusarium species in cereals. However, their practical use is facing limitations such as high volatility, UV sensitivity, and fast oxidation. Encapsulation techniques are supposed to provide protection to the EOs and control their release into the environment. Ammoides pusilla essential oil (AP-EO) proved to be an efficient inhibitor of Fusarium avenaceum growth and its enniatins (ENNs) production. In the present work, AP-EO was encapsulated, using the impregnation method, into mesoporous silica particles (MSPs) with narrow slit pores (average diameter = 3.1 nm) and coated with chitosan. In contact assays using an agar medium, the antifungal activity of AP-EO at 0.1 µL mL−1 improved by three times when encapsulated into MSPs without chitosan and the ENNs production was significantly inhibited both in coated and non-coated MSPs. Controls of MSPs also inhibited the ENNs production without affecting the mycelial growth. In fumigation experiments assessing the activity of the EO volatile compounds, encapsulation into MSPs improved significantly both the antifungal activity and ENNs inhibition. Moreover, coating with chitosan stopped the release of EO. Thus, encapsulation of an EO into MSPs improving its antifungal and antimycotoxin properties is a promising tool for the formulation of a natural fungicide that could be used in the agriculture or food industry to protect plant or food products from the contamination by toxigenic fungi such as Fusarium sp. and their potential mycotoxins.